Executive summary from American Radium Society's appropriate use criteria on neurocognition after stereotactic radiosurgery for multiple brain metastases. Issue 12 (11th August 2020) - Milano, Michael T; Chiang, Veronica L S; Soltys, Scott G; Wang, Tony J C; Lo, Simon S; Brackett, Alexandria; Nagpal, Seema; Chao, Samuel; Garg, Amit K; Jabbari, Siavash; Halasz, Lia M; Gephart, Melanie Hayden; et al.
Abstract: Background: The American Radium Society (ARS) Appropriate Use Criteria brain malignancies panel systematically reviewed (PRISMA [Preferred Reporting Items for Systematic Reviews and Meta-Analyses]) published literature on neurocognitive outcomes after stereotactic radiosurgery (SRS) for patients with multiple brain metastases (BM) to generate consensus guidelines. Methods: The panel developed 4 key questions (KQs) to guide systematic review. From 11 614 original articles, 12 were selected. The panel developed model cases addressing KQs and potentially controversial scenarios not addressed in the systematic review (which might inform future ARS projects). Based upon quality of evidence, the panel confidentially voted on treatment options using a 9-point scale of appropriateness. Results: The panel agreed that SRS alone is usually appropriate for those with good performance status and 2–10 asymptomatic BM, and usually not appropriate for >20 BM. For 11–15 and 16–20 BM there was (between 2 case variants) agreement that SRS alone may be appropriate or disagreement on the appropriateness of SRS alone. There was no scenario (among 6 case variants) in which conventional whole-brain radiotherapy (WBRT) was considered usually appropriate by most panelists. There were several areas of disagreement, including: hippocampal sparing WBRT for 2–4 asymptomatic BM; WBRT for resected BM amenable to SRS; fractionated versus single-fraction SRS for resected BM, larger targets, and/or brainstem metastases; optimal treatment (WBRT, hippocampal sparing WBRT, SRS alone to all or select lesions) for patients with progressive extracranial disease, poor performance status, and no systemic options. Conclusions: For patients with 2–10 BM, SRS alone is an appropriate treatment option for well-selected patients with good performance status. Future study is needed for those scenarios in which there was disagreement among panelists.